Toxicological effects induced by the biocide triclosan on Pseudokirchneriella subcapitata - Machado, Maria Manuela Dias (2021)
Triclosan, a widely used biocide broadly found in aquatic environments, is cause of concern due to its unknown effects on non-targets organisms. In this study, a multi biomarker approach was used in order to evaluate the 72?h-effect of triclosan on the freshwater alga Pseudokirchneriella subcapitata. Triclosan, at environmental relevant concentrations (27 and 37?µg L-1), caused a decrease of proliferative capacity, which was accompanied by an increase of cell size and a profound alteration of algae shape. It was found that triclosan promoted the intracellular accumulation of reactive oxygen species, the depletion of non-enzymatic antioxidant defenses (reduced glutathione and carotenoids) and a decrease of cell metabolic activity. A reduction of photosynthetic pigments (chlorophyll a and b) was also observed. For the highest concentration tested (37 µg L-1), a decrease of photosynthetic efficiency was detected along with a diminution of the relative transport rate of electrons on the photosynthetic chain. In conclusion, triclosan presents a deep impact on the microalga P. subcapitata morphology and physiology translated by multiple target sites instead of a specific point (cellular membrane) observed in the target organism (bacteria). Additionally, this study contributes to clarify the toxicity mechanisms of triclosan, in green algae, showing the existence of distinct modes of action of the biocide depending on the microalga.